Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1136/annrheumdis-2012-203095
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90 (Hsp90) inhibition targets canonical TGF-β signalling to prevent fibrosis

Abstract: Objectives Targeted therapies for systemic sclerosis (SSc) and other fibrotic diseases are not yet available. We evaluated the efficacy of heat shock protein 90 (Hsp90) inhibition as a novel approach to inhibition of aberrant transforming growth factor (TGF)-β signalling and for the treatment of fibrosis in preclinical models of SSc. Methods Expression of Hsp90 was quantified by quantitative PCR, western blot and immunohistochemistry. The effects of Hsp90 inhibition were analysed in cultured fibroblasts, in bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 40 publications
5
61
0
Order By: Relevance
“…These future investigations could yield some relevant information about the role of Hsp90 in MMP and, together with already existing knowledge on the powerful anti-inflammatory and anti-scarring effects of anti-Hsp90 treatment [14][15][16][17][18][19][20][21]25,[28][29][30], possibly support the introduction of nontoxic Hsp90 inhibitors for future medical management of patients with this potentially devastating disease that may otherwise cause permanent damage when therapy is delayed or ineffective.…”
Section: The Hypothesis and Its Evaluation And Implicationmentioning
confidence: 86%
See 2 more Smart Citations
“…These future investigations could yield some relevant information about the role of Hsp90 in MMP and, together with already existing knowledge on the powerful anti-inflammatory and anti-scarring effects of anti-Hsp90 treatment [14][15][16][17][18][19][20][21]25,[28][29][30], possibly support the introduction of nontoxic Hsp90 inhibitors for future medical management of patients with this potentially devastating disease that may otherwise cause permanent damage when therapy is delayed or ineffective.…”
Section: The Hypothesis and Its Evaluation And Implicationmentioning
confidence: 86%
“…Based on the above, we hypothesize that pharmacological Hsp90 blockade could represent a double-edged sword in the treatment of MMP by pleiotropic targeting of the mentioned Hsp90 inhibitor-prone pathophysiological factors involved in both inflammatory subepidermal blister formation and cicatricial processes [19][20][21]25,[28][29][30]. Due to their additional anti-cancer activity, Hsp90 inhibitors could even be proclaimed as a triple-edged sword against the malignancy-associated anti-laminin 332 subtype of MMP [12].…”
Section: The Hypothesis and Its Evaluation And Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is reported by Sibinska and some other researchers that activation of interstitial lung fibroblast and presence of extracellular matrix production are pathological features of pulmonary fibrosis, and the effect of TGF-β1 on the pathological changes is mainly mediated through the TGF-β/Smads signaling pathway. Moreover, the anti-fibrosis effect of heat shock protein HSP90 is related to TGF-β receptor destruction and inhibition of Smad2/3 activation (7,8). So, it is thought that the role of TGF-β and its downstream cytokines in PSP bullae might induce pulmonary fibrosis.…”
Section: Original Articlementioning
confidence: 99%
“…Our recent findings (26) as well as those of other groups have indicated that Hsp90 is a critical modulator of fibrosis via alteration of the TGF␤ signaling pathway (27)(28)(29)(30). To further develop this line of research, the present study was designed to look into the possible role of Hsp90 in STAT-3-mediated fibrotic signaling during cardiac hypertrophy and associated fibrosis.…”
mentioning
confidence: 94%